Changing Perceptions of Ornamental Plants in Urban Yangon, Myanmar - Aung Si; Aung Kyawphyo (Plants, 2025)
Gardening is a popular pastime for people from all walks of life in Yangon, the most populous city of Myanmar and its former capital. The cultivation of ornamental plants has continued uninterrupted despite decades of social and political crises that have plagued the country, but there are indications that people’s tastes have changed considerably. These changing tastes are documented here through interviews of nursery owners and amateur gardeners from Yangon. This study also investigates the development of naming patterns in Burmese, in particular the names coined for recently introduced plants. A total of 176 older and 156 newer (introduced over the last two decades) ornamental plants grown in Yangon were documented; of the former category, 75% were still available in nurseries, whereas the rest were no longer popular. The newer plants had significantly fewer unanalysable names than the older plants, suggesting a modern preference for descriptive/allusive labels. This also applies to native, wild-harvested orchid species. Many of the newer, introduced orchid hybrids have not been given Burmese names, but are only referred to by shorthand labels like dendro and vanda. This study provides a first, linguistically informed ethnobiological report of ornamental plants in Myanmar.